Background Note on the Proposals of Ministry of Coal for Annual Plan 1995-96 January, 1995 - Planning Commission (Power and Energy Division Planning Commission Government of India, 1995)
The Background Note on the Ministry of Coal’s proposals for the Annual Plan 1995-96 provides a detailed overview of India’s coal and associated power sector initiatives within the Eighth Plan framework. The report assesses past performance, highlights operational challenges, and outlines strategies to enhance productivity, environmental sustainability, and financial efficiency. Key observations include shortfalls in coal consumption and production, rising demand in the power and steel sectors, and the need for improved project implementation through timely land acquisition and environmental clearances. Proposed measures focus on increasing productivity per man-shift, maximizing indigenous coking coal, modernizing mining technologies, and implementing comprehensive environmental programs. The financial plan for 1995-96 involves an outlay of ₹3,463.79 crores, supporting both mining and non-mining projects, including infrastructure modernization and expansion schemes. The document emphasizes operational efficiency, private sector participation, and foreign collaboration to meet the growing energy demands of a developing economy while ensuring sustainable resource management.
Government of India Planning Commission Power and Energy Division (Coal Unit)
Keywords: Coal Sector; Annual Plan 1995-96; Mining Productivity; Coal India Limited; Coking Coal; Non-Coking Coal; Environmental Sustainability; Coal Washery; Power Sector; Financial Outlay; Project Implementation; Technological Modernization